Influence of Resource Based Management on Strategic Renewal of Insurance Firms in Kenya - Karani, Frida W.; Ogutu, Martin (Strategic Journals, 2018)
The objective of the study was to determine the effect of resource based management on the strategic renewal of insurance firms in Kenya. Two dimensions of strategic renewal were studied: the insurance firms’ deliberate plans to imitate strategic renewal and strategic renewal by introduction of new products and product rebranding. The target population was operative managers in 53 insurance firms. The sample size was 5 operative managers in 47 insurance firms resulting to a sample size of 235 respondents. The study used simple random sampling in the determination of respondents and used the Cochran’s formula to determine sample size. The Likert scale questionnaire was used to collect data which was analyzed using descriptive and inferential statistics which were spearman’s correlation and linear regression. Results of ANOVA, goodness of fit were used to make findings and conclusions about the study. Kuder-Richardson (KR21) and Cronbach’s alpha was used to measure reliability of the research instrument. The results of regression showed that resource based management had influence on strategic renewal of insurance firms in Kenya. However different facets of strategic renewal are affected differently which may reflect a divergent view on how the model should be employed. A significant influence was reported for impact of resource based management on deliberate plans to initiate renewal and a not statistically significant relationship was reported for impact of resource based management on implementation of strategic renewal by introduction of new products and product rebranding. The study therefore recommended that insurance firms’ managers should endevour to create more sustainable VRIO attributes for their firms. They should also consider renewing their resources alongside using resources for renewal. The study was grounded on the dynamic capabilities theory which explains the link between a firm’s inward resource capabilities its ability to work with those capabilities to initiate strategic renewal.
Keywords: Resource Based Management; Resource valuability; Resource rarity; Resource substitutability; Resource dynamism; Strategic Renewal